Correlations Between Leaf N, P, K, Ca and Fe Levels and The Production of Metabolites in Torbangun (Coleus amboinicus Lour.) - Mulyana, Erik; Aziz, Sandra A; Aisyah, Syarifah Iis; Damanik, M. Rizal Martua (Department of Agronomy and Horticulture, IPB University, 2015)
Torbangun (Coleus amboinicus Lour) is a tropical plant from the Lamiaceae family. Torbangun leaves have a distinct aroma. Torbangun leaves have been traditionally used as a medicinal plant in North Sumatra, Indonesia. Bataknese lactating women in North Sumatra consumed torbangun leaves after giving birth with beliefs that it could increase their breast milk production (lactagogue), and that the leaves can function as anti-fungal and/or anti-bacterial, analgesic, to reduce blood cholesterol, and clean the human uterus. However, scientific evidence on this traditional herb is limited. This research was conducted to: (1) determine the leaf N, P, K, Ca and Fe in different position along the plant and the leaf age as to diagnose the secondary metabolites content of torbangun leaves, and (2) determine the relationship between N, P, K, Ca and Fe leaf concentrations with their metabolite production. The results of the study showed that: (1) the best leaf position and age to determine of the need of N, P, K, Ca and Fe nutrients are on the 3rd leaf position of 5 months-old plant (2) There was a positive correlation between leaf K concentrations with shoot dry weight, Ca with PAL activity, and Fe with total saponins on the 3rd leaf position of 5 months-old plant.Keywords: Coleus amboinicus Lour, torbangun, nutrient, correlation test, secondary metabolites.